(untitled) (Journal of Bangladesh Academy of Sciences, 2023)
Soybean genotypes G00006, BD2336, AGS383, PK472, BCS1, NCS1, BU Soybean1 and BARI Soybean6 were evaluated under 20% (drought) and 80% (control) of field capacity based on morpho-physiological and yield response to drought. The results revealed that plant height, leaf number, chlorophyll content, photosynthesis, stomatal conductance, transpiration rate, relative water content and water uptake capacity of soybean drastically reduced due to drought. However, root: shoot ratio increased under drought condition. Across the genotypes, the root : shoot ratio ranged from 0.20 to 0.47 in control, while 0.22 to 59 in drought condition. Genotypes BD2336, AGS383 and G00006 produced higher number of pods and seeds, whereas minimum yield reduction was recorded in AGS383 under drought. Based on drought tolerance index, AGS383 ranked 1st, while BD2336 and PK472 ranked 2nd and 3rd position, respectively. High grain yielding ability of AGS383 suggested that it could be cultivated in drought prone environment. J. Bangladesh Acad. Sci. 47(2); 223-240: December 2023